The importance of individual participation for collective success in video games: collaborative experiences in March of Empires (Simbiótica. Revista Eletrônica, 2025)
This article analyzes the importance of individual participation for collective success in video games, based on a qualitative approach that combines a netnographic study of the game March of Empires — available for PC and mobile devices — and interviews with ten members of the alliance The Belgians. Authors such as Aarseth, Atique, Lupton, Juul, and Huizinga understand these artifacts as sociocultural phenomena, highlighting the historical role of games as “magic circles” and the relevance of online communities as spaces of belonging and sociability. The study focuses on the structure and functioning of gaming communities from the perspective of collaboration, understood as a fundamental element both for the success of the alliance and for maintaining cohesion among its members. Joining an alliance allows players to grow and evolve more rapidly, but this process requires mutual and continuous commitment.
Keywords: digital sociology; cyberculture; electronic games; virtual communities